Pengaruh Corporate Social Responsibility (CSR), Struktur Modal, Manajemen Aset dan Sales Growth terhadap Kinerja Keuangan pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022 - Afifah, Zulfa Dwi Nur’ainni; Priantilianingtiasari, Ruly (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Financial performance is the company's ability to manage and control its resources. The purpose of this study is to analyze the effect of Corporate Social Responsibility (CSR), Capital Structure, Asset Management, and Sales Growth on financial performance in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2022. The type of data used in this study is secondary data. The samples used were 32 manufacturing companies in the Industrial and Chemical sectors. The method used in the research is quantitative method by applying purposive sampling technique. The data analysis techniques in this study are classical assumption test, multiple linear regression analysis, hypothesis testing and coefficient of determination. The results of this study show that CSR, capital structure and sales growth have a significant effect on financial performance, while asset management has no significant effect on financial performance. Keywords : Corporate Social Responsibility, Financial Performance, Asset Management, Sales Growth, Capital Structure.